The Behavior of Adolescent Online Game Players: An Analysis of the Impact of Peer Interaction - Nurhartanti, Wulan; Oktaviani, Maya; Zulfa, Vania (Asosiasi Asesmen Pendidikan (AAP), 2024)
The study aims to determine how much influence peer interaction has on the behavior of adolescents who like to play garena free fire online games using associative quantitative research methods with data collection methods using google form. The research location was Bekasi city and took place from February 2024 - June 2024. Respondents in this study amounted to 150 teenagers with criteria for adolescents aged 15-18 years, domiciled in Bekasi City, playing GFF online games. The sampling technique used purposive sampling. This study used the Peer Relationship Scale for Adolescent: a validity and reliability study Aydogdu (2022) instrument for peer interaction and Motives for online gaming questionnaire (MOGQ) Demetrovics et al. (2011) for adolescent behavior. The data analysis technique used is a significant regression test of Fhitung > Ftabel = 17.460 > 3.934, meaning that there is a significant influence between peer interaction on the behavior of adolescents who like to play garena free fire online games. Furthermore, the result of the coefficient of determination (R2) is 0.106 or equal to 10.6%, so it can be concluded that the contribution of peer interaction to the behavior of adolescents who like to play online games garena free fire is 10.6%. Peer interaction has an influence on the behavior of teenagers who like to play garena free fire online games. Teenagers who have high peer interactions will also have high adolescent behavior in playing garena free fire online games.